IDENTIFICATION AND QUANTIFICATION OF MAJOR POLYPHENOLS IN DIFFERENT TYPES OF OLIVE OIL: A SYSTEMATIC REVIEW OF HEALTH BENEFITS - Suryandari, Mercyska; Isdianto, Andik; Fitrianti, Novariza (International Islamic Medicine Forum, 2024)
Olive oil is a key component of the Mediterranean diet, renowned for its flavor and health benefits, especially for its polyphenol content. These polyphenols have strong antioxidant properties, protecting cells from oxidative stress and reducing the risk of chronic diseases such as cardiovascular disease, cancer, and neurodegenerative disorders. This study aims to systematically identify and quantify the main polyphenols in different types of olive oil, including Extra Virgin Olive Oil (EVOO), Virgin Olive Oil (VOO), Refined Olive Oil (ROO), Pure Olive Oil (POO), and Pomace Olive Oil. Using a qualitative approach and descriptive analysis, a comprehensive literature study was conducted to collect and evaluate research on polyphenol content in various olive oils. The results showed significant differences in polyphenol profiles. EVOO, which is produced through cold pressing without heat or chemicals, has the highest polyphenol content, offers superior health benefits and complex flavors. VOO, although more processed, still contained moderately high polyphenols, suitable for medium temperature cooking. ROO, which is extensively processed, has lower polyphenol levels, ideal for high temperature cooking but with fewer health benefits. POO, a blend of VOO and ROO, offers a balance of flavor and practicality. Pomace Olive Oil, with the lowest polyphenol content, is used mainly for industrial frying due to its high smoke point. In conclusion, this study emphasizes the importance of choosing the type of olive oil based on its use and health benefits. EVOO is optimal for raw or lightly cooked dishes, VOO for all- purpose cooking, and ROO and Pomace Olive Oil for high temperature applications. This research guides consumers and manufacturers in making the right choice to optimize the health benefits of olive oil.